1952
DOI: 10.1152/ajplegacy.1952.171.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Action of Salicylates and Related Drugs on Inflammation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1955
1955
1974
1974

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Wounds Treated With Sodium Salicylate.--This drug was used because it has been demonstrated to be an inhibitor of both pepsin (18) and fibrinolysin (19), two very different kinds of proteases. Furthermore, Ungar has shown that in guinea pig liver slices and skin slices sodium salicylate inhibits the proteolysis caused by anaphylactic and anaphylactoid agents (12) and by burning (11).…”
Section: Group I1 Wounds Treated With Sodium Sal@ylate or With Soybementioning
confidence: 99%
See 1 more Smart Citation
“…Wounds Treated With Sodium Salicylate.--This drug was used because it has been demonstrated to be an inhibitor of both pepsin (18) and fibrinolysin (19), two very different kinds of proteases. Furthermore, Ungar has shown that in guinea pig liver slices and skin slices sodium salicylate inhibits the proteolysis caused by anaphylactic and anaphylactoid agents (12) and by burning (11).…”
Section: Group I1 Wounds Treated With Sodium Sal@ylate or With Soybementioning
confidence: 99%
“…Both soybean trypsin inhibitor and sodium salicylate suppress fibrinolysin (15,19), both prevent the proteolysis in tissue slices produced by burning …”
Section: B Wounds Treated With Soybean Trypsinmentioning
confidence: 99%
“…Among the compounds tested were sodium salicylate which was found to inhibit fibrinolysin in vitro (12), a crystalline protein isolated from soybean by Kunitz r (13) and which 7 General Biochemicals, Inc., Chagrin Falls, Ohio.…”
Section: P R O T E O L Y S I S a N D H I S T A M I N E R E L Ementioning
confidence: 99%
“…M en o n [11] initiated an in vestigation on the in vivo role of soluble aspirin in fibrinolysis and found that aspirin enhanced the euglobulin lysis time in six volunteers after the ad ministration of 1,200 mg of soluble aspirin 24 h prior to the testing. It has been reported, however, that in vitro, anti-inflammatory substances either inhibit fibrinolysis [4,13], which may play an important role in the devel opment of inflammation, or under specific conditions enhance fibrinolytic activity [3,14], The present investigation, therefore, was undertaken in order to further study and elucidate the in vitro effect of aspirin in the blood fibrinolytic mechanism.…”
Section: Introductionmentioning
confidence: 99%